Math, asked by dipannita77752, 7 months ago

The coefficient of  x^3 in the expansion of  m^3(1-x/m)^3 is:​

Answers

Answered by shadowsabers03
5

The (r+1)^{th} term in the expansion of m^3\left(1-\dfrac{x}{m}\right)^3=(m-x)^3 is,

\longrightarrow T_{r+1}=\,^3C_r\ m^{3-r}\ (-x)^r

\longrightarrow T_{r+1}=(-1)^r\cdot\,^3C_r\ m^{3-r}\ x^r

The coefficient in the (r+1)^{th} term,

\longrightarrow C_{r+1}=(-1)^r\cdot\,^3C_r\ m^{3-r}

To find coefficient of x^3, we need to equate the exponent of x to 3, i.e.,

\longrightarrow r=3

So the 4th term contains x^3, and the coefficient of x^3 is,

\longrightarrow C_4=(-1)^3\cdot\,^3C_3\ m^{3-3}

\longrightarrow\underline{\underline{C_4=-1}}

Hence -1 is the answer.

Similar questions